Determining the rotational velocity of gas-metal multicomponent plasma in a reflex discharge - Kovtun, Yu.V.; Skibenko, A.I.; Skibenko, E.I.; Larin, Yu.V.; Yuferov, V.B. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
For the first time the rotational velocity of plasma layers with np = ncr^1,2 in the gas-metal plasma medium of the reflex discharge was determined using the two-frequency microwave fluctuation reflectometry. The measurement results demonstrated that the angular frequency of plasma layer rotation is varying and therefore the plasma rotates not as a single whole. The maximum rotation velocity increases with magnetic field increasing. The values of the electric field strength in two layers and the plasma particle separation coefficient α were determined. Впервые для определения скорости вращения плазменных слоев с np = ncr^1,2 в среде газометаллической плазмы отражательного разряда была применена двухчастотная СВЧ-флуктационная рефлектометрия. Результаты измерений показали, что угловая частота вращения плазменных слоев различна и, таким образом, плазма вращается не как единое целое. Максимальная скорость вращения увеличивается с увеличением магнитного поля. Проведены оценки величин напряженности электрического поля в двух слоях и коэффициента α разделения частиц плазмы. Вперше для визначення швидкості обертання плазмових прошарків з np = ncr^1,2 в середовищі газометалевої плазми відбивного розряду була застосована двохчастотна НВЧ-флуктаційна рефлектометрія. Результати вимірювань показали, що кутова частота обертання плазмових прошарків різна і, таким чином, плазма обертається не як єдине ціле. Максимальна швидкість обертання збільшується зі збільшенням магнітного поля. Проведено оцінки величин напруженості електричного поля в двох прошарках і коефіцієнта α розділення частинок плазми.